2016
DOI: 10.1021/acscatal.6b00564
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on the Mechanism of Formic Acid Decomposition by a Well-Defined Bifunctional Cyclometalated Iridium(III) Catalyst: Self-Assisted Concerted Dehydrogenation via Long-Range Intermolecular Hydrogen Migration

Abstract: DFT calculations have been performed to gain insight into the mechanism of formic acid (HCOOH) decomposition into H 2 and CO 2 , catalyzed by a well-defined bifunctional cyclometallated iridium(III) complex (a Ir-H hydride) based on 2-aryl imidazoline ligand with a remote NH functionality. It is shown that the reaction features the direct protonation of the Ir-H hydride by HCOOH with the hydrogen shuttling between the NH group and the carbonyl group of HCOOH. Importantly, the simultaneous presence of two HCOOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…43 Last but not least, previous investigations on FA dehydrogenation using noble metal complexes pointed out several subtle aspects that should be mentioned here. The computational studies performed by Zhang et al 44 showed the capacity of formic acid to form stable dimers. As a result, the transition state leading to the hydride protonation would be assisted by the N-H moiety.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…43 Last but not least, previous investigations on FA dehydrogenation using noble metal complexes pointed out several subtle aspects that should be mentioned here. The computational studies performed by Zhang et al 44 showed the capacity of formic acid to form stable dimers. As a result, the transition state leading to the hydride protonation would be assisted by the N-H moiety.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…However, theoretical calculations performed by Zhang et al discard the pathway proposed by Xiao's group and suggest an alternative mechanism by which two molecules of FA are required – one acts as hydrogen source and the other as H‐shuttle (Figure ) . This mechanism is based on the capacity of FA molecules to form stable dimers in solution by means of hydrogen bonding interactions, since a single FA molecule is incapable of linking the two sites of the bifunctional catalysts (namely, Ir and NH) .…”
Section: Iridium Catalystsmentioning
confidence: 99%
“…Mechanistic studies suggest the long‐range metal‐ligand cooperation between FA and the distal NH functional group from the imidazole moiety. The subsequent computational study by Zhang's group corroborated the reaction mechanism involving two FA molecules, where one acts as a H 2 source, and the other participates as a proton shuttle to favor the long‐range activation ( 8‐TS , Figure ).…”
Section: Catalysts With Bidentate C N‐/n N‐type Ligandsmentioning
confidence: 82%